Competitive priorities and human resources management at auto parts companies - Guimaraes, Marcia Regina Neves; Teodoro Filho, Alberto Magno (Revista Gestão da Produção Operações e Sistemas, 2012)
Considering the importance of studies on operation strategies, this work has the goal of discussing aspects related to human resources and their coherence with competitive priorities at four auto part companies in the Sorocaba, SP, region. The results were obtained by means of semi-open interviews and direct observations conducted during visits to the companies. Even considering the need for further studies for a more in-depth discussion, we concluded that Unit A is the one with most coherence between the decision area related to human resource management and competitive priorities. In Units B and C factors like greater autonomy for production workers could offer better support to competitive priorities. Unit D is the only one that favors costs, which could justify why it is the organization closest to the vision of control and command.Keywords: operation strategies; human resources management, competitive priorities; auto parts industry.